Effects of Planetary Parameters on Disequilibrium Chemistry in Irradiated Planetary Atmospheres: From Gas Giants to Sub-Neptunes - Sagnick Mukherjee; Jonathan J. Fortney; Nicholas F. Wogan; David K. Sing; Kazumasa Ohno (The Astrophysical Journal)
A primary goal of characterizing exoplanet atmospheres is to constrain planetary bulk properties, such as their metallicity, C/O ratio, and intrinsic heat. However, there are significant uncertainties in many aspects of atmospheric physics, such as the strength of vertical mixing. Here, we use PICASO and the photochem model to explore how atmospheric chemistry is influenced by planetary properties such as metallicity, C/O ratio, T _int , T _eq , and K _zz in hydrogen-dominated atmospheres. We vary the T _eq of the planets between 400 and 1600 K, across “cold,” “warm,” and “hot" objects. We also explore an extensive range of T _int values between 30 and 500 K, representing sub-Neptunes to massive gas giants. We find that gases such as CO and CO _2 show a drastically different dependence on K _zz and C/O for planets with cold interiors (e.g., sub-Neptunes) compared to planets with hotter interiors (e.g., Jupiter mass planets) for the same T _eq . We also find that gases such as CS and CS _2 can carry a significant portion of the S-inventory in the upper atmosphere near T _eq ≤ 600 K, below which SO _2 ceases to be abundant. For solar C/O, we show that the CO/CH _4 ratio in the upper atmospheres of planets can become ≤1 for planets with low T _eq , but only if their interiors are cold ( T _int ≤ 100 K). We find that photochemical haze precursor molecules in the upper atmosphere show very complex dependence on C/O, K _zz , T _eq , and T _int for planets with cold interiors (e.g., sub-Neptunes). We also briefly explore fully coupling PICASO and photochem to generate self-consistent radiative–convective–photochemical-equilibrium models.